2016
DOI: 10.1089/vbz.2016.2028
|View full text |Cite
|
Sign up to set email alerts
|

First Report onToxoplasma gondiiInfection in Bosnia and Herzegovina: Study in Blood Donors

Abstract: This study provided the first data on the prevalence of Toxoplasma infection in B&H, as well as insight into the demographic risk factors as a basis for a future prevention program for Toxoplasma infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
1
5
4
Order By: Relevance
“…In accordance with previous studies conducted on blood donors [ 19 , 22 ], we have also found that the prevalence increases with age, obviously as a result of the cumulative effect of exposure to the parasite over the years. This increase in the infection prevalence is linear, but, unlike the Bosnia and Herzegovina study [ 19 ], in this study, it was detected in both genders, ranging from 8.7% in the youngest age group (18–29 years) to 39.6% in the oldest (>60 years). For the first time in Serbia, we analyzed the prevalence of T. gondii infection in healthy adult males and showed it has matched or surpassed the prevalence in female donors of the same age, albeit not significantly.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with previous studies conducted on blood donors [ 19 , 22 ], we have also found that the prevalence increases with age, obviously as a result of the cumulative effect of exposure to the parasite over the years. This increase in the infection prevalence is linear, but, unlike the Bosnia and Herzegovina study [ 19 ], in this study, it was detected in both genders, ranging from 8.7% in the youngest age group (18–29 years) to 39.6% in the oldest (>60 years). For the first time in Serbia, we analyzed the prevalence of T. gondii infection in healthy adult males and showed it has matched or surpassed the prevalence in female donors of the same age, albeit not significantly.…”
Section: Discussionsupporting
confidence: 92%
“…According to worldwide data, one third of them (33%) may be considered to be chronically infected with T. gondii [ 17 ], but the prevalence of infection varies greatly among countries. However, the overall prevalence of toxoplasmosis of 20.5% detected in this study is much lower than that reported among blood donors in the neighboring countries—Croatia (47.8% and 53.8%) [ 18 ] and Bosnia and Herzegovina (30.6%) [ 19 ]—in the past decade. The diagnostic algorithm for toxoplasmosis and methodology applied in our study is widely used in Reference Laboratories for Toxoplasmosis throughout Europe.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…23 Infection with T. gondii has been detected in blood donors. [24][25][26] However, the extent of the association between blood transfusion and infection with T. gondii remains unclear. To the best of our knowledge, no case-control study has been performed to investigate this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasma parasitemia could be diagnosed using blood smears examination and by polymerase chain reaction . T gondii infection has been distinguished in blood donors and previous studies reported a correlation between Toxoplasma infection and blood transfusion and recommended molecular screening for Toxoplasma infection before blood transfusion especially in the immunocompromised patients …”
Section: Introductionmentioning
confidence: 99%